War and Resentment: Critical Reflections on the Legacies of the Iran-Iraq War. Issue 1 (2nd January 2017) - Ehsani, Kaveh
Abstract: During the challenging transitional period after the 1979 revolution, the Iran-Iraq War helped the Islamic Republic to consolidate its hold on power by creating new institutions of coercion and governance, mobilizing popular support, and eliminating domestic rivals. Despite the state becoming entrenched, the political elite and Iranian society both remain highly divided over the legacy of the war and the nature and the direction of the post-revolution and post-war project. The popular aspirations that were unleashed during the revolution were incorporated into the war experience, but they remain unfulfilled and are a major factor that shape public culture and political practices. This discontent is compounded by the shortcomings of authoritarian and ill-conceived post-war reconstruction, especially in war-torn regions. The imposition of an official interpretation of the 'Sacred Defense' effectively silences plural experiences of the war and alternative and more critical analyses of it. As a result, instead of acting as a unifying experience that reinforces state hegemony, the legacy of the war is a widespread resentment that affects public culture and political attitudes. This article investigates the conflicted legacies of the Iran-Iraq War by using case studies from historical and ethnographic research, as well as professional experiences (Much of the analysis in this article is based on the author's academic research and professional experience in Iran during extended intervals since 1989. These include ethnographic research and professional work as a regional planner on post-war reconstruction in rural Khuzestan; ongoing historical and ethnographic research on the refinery city of Abadan; urban research and consulting collaboration with the Tehran City Council and other urban institutions; and ongoing editorial collaboration with the journal Goftogu in Tehran).